2012
DOI: 10.4103/0253-7176.106020
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Substance Use: A Comparative Study of Alcohol Use in Tribals and Non-tribals

Abstract: Background:Consumption of alcohol has been attributed to different reasons by consumers. Attitude and knowledge about the substance and addiction can be influenced by the cultural background of the individual. The tribal population, where alcohol intake is culturally accepted, can have different beliefs and attributes causing one to take alcohol. This study attempts to examine the reasons for alcohol intake and the belief about addiction and their effect on the severity of addiction in people with a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 7 publications
1
22
1
Order By: Relevance
“…Financial problems, illness/injury to self or to someone in the family, and death of a loved one were the commonest stressors associated with moderate/severe depression, similar to earlier research [32]. Lifetime alcohol use had a high prevalence and some reasons suggested for higher consumption among tribal populations are increased poverty, illiteracy, increased stress, and peer pressure [36]. …”
Section: Discussionsupporting
confidence: 74%
“…Financial problems, illness/injury to self or to someone in the family, and death of a loved one were the commonest stressors associated with moderate/severe depression, similar to earlier research [32]. Lifetime alcohol use had a high prevalence and some reasons suggested for higher consumption among tribal populations are increased poverty, illiteracy, increased stress, and peer pressure [36]. …”
Section: Discussionsupporting
confidence: 74%
“…4 Manimunda et al also found that alcohol intake with rest of the population was statistically significant in tribal population. 3 Mohindra K also found alcohol consumption in India is disproportionately higher among poorer and socially marginalized groups, notably scheduled tribes (STs).…”
Section: Discussionmentioning
confidence: 90%
“…3 V. S. Sreeraj, Surjit Prasad, Christoday Raja Jayant Khess and N. A. Uvais, study conducted among the tribal of Jharkhand. 4 NNMB in its technical report no: 24, NIH, Indian Council of Medical Research (ICMR) reported that alcohol consumption were significantly (p<0.001) associated with hypertension among tribal population in their study in nine states of India. 1 Todkar SS et al found a significant association of alcohol intake & hypertension among rural people.…”
Section: Introductionmentioning
confidence: 99%
“…Which signals the failure of law system, this finding is in congruent with Meena et al while Sumit et al reported corresponding it as 24 year. 30,21 Basu et al reported as 18 years, while contradictory with deswal et al 34,35 When inquired about reason for alcohol use, 45% explained it for enjoyment and 29.5% were consuming for escaping from pain, work stress as well for social company and 25.2% were due to peer pressure. These findings were similar to study by Ramanan et al in which 44.4% used alcohol for fun while inconsistent findings were reported by Sreeraj et al and Meena et al i.e.…”
Section: Pattern Of Alcohol Consumptionmentioning
confidence: 96%